Effect of exclosure on subsurface water level and sediment yield in the tropical highlands of Ethiopia. (1st September 2022) - Yibeltal, Mesenbet; Tsunekawa, Atsushi; Haregeweyn, Nigussie; Meshesha, Derege Tsegaye; Billi, Paolo; Bedaso, Zelalem; Wubet, Anteneh; Kang, Min Woo; Lee, Sang Soo
Abstract: Grazing is a major cause of soil erosion and land degradation across many parts of Ethiopia. This study examined the effects of exclosure on subsurface water levels, soil erosion, and the relationship between daily rainfall and subsurface water levels. Piezometers were used to measure subsurface water levels in the exclosure area during 2017–2020. We found that sediment yield, runoff, and the volume of subsurface water vary greatly depending on the exclosure and temporal practices used. Exclosure of grazing land was the most effective sustainable land management practice in reducing runoff and sediment yield. In 2019 and 2020, the subsurface water level continued to rise at piezometers with exclosure, which shows that exclosure contributed to the subsurface water level rising. In addition, piezometers in grazing land and the exclosure indicate that runoff trapped by acacia decurrens trees can contribute to significant differences in subsurface water levels. Higher runoff coefficients were observed in 2017 and 2018 than in 2019 and 2020, indicating that the exclosure greatly affects runoff; therefore, its implementation is vital to reduce runoff and enhance water conservation. Sediment yields measured for 2017, 2018, 2019, and 2020 were 140.45, 133.15, 101.03, and 74.39 g L −1 day −1, respectively. In 2017 and 2018, sediment yield increased, while in 2019 and 2020 sediment yield decreased because of an exclosure around the gully's cross-section and communal grazing. This study shows that erosion is reduced by exclosure, possibly due to the restoration of protective vegetation cover. This study revealed that a minimum of human and livestock intervention during the study period considerably increased groundwater levels and decreased soil erosion. Generally, the results of this study indicated that exclosure has a considerable impact on runoff and sediment. Therefore, exclosure implementation is vital to reduce runoff and sediment and enhance water conservation, thus supporting the development of effective communal grazing land management measures on the study sites and other similar environmental settings. Graphical abstract: A comparison of changes in grazing land cover with Acacia decurrens between 2017 and 2020 following the implementation of exclosure practices (photos on the left), and corresponding subsurface water level (graphs on the right), where P1–P20 stands for Piezometer number from 1 to 20. Image 1 Highlights: In the tropical highlands, communal grazing leads to land degradation. Exclosure facilitates subsurface water recharge. In high rainfall areas, exclosure reduces runoff from grazing lands. Exclosure reduces sediment yield from tropical highlands grazing lands. Grazing land exclosure prevents the degradation of land resources.